An aqueous rechargeable sodium−magnesium mixed ion battery based on NaTi2(PO4)3–MnO2 system. (10th July 2019) - Liu, Zongxiao; Pang, Gang; Dong, Shengyang; Zhang, Yadi; Mi, Changhuan; Zhang, Xiaogang
Abstract: In order to develop an aqueous battery with high specific capacity, we synthesized NaTi2 (PO4 )3 anode material and MnO2 cathode material, and studied the electrochemical properties of the two materials in Na2 SO4, MgSO4 and Na2 SO4 −MgSO4 mixed aqueous electrolytes, respectively. The results show that MnO2 has excellent electrochemical properties in electrolyte containing Mg 2+ and its specific capacity can reach about 100 mAh g −1 . Na + and Mg 2+ can be intercalated/deintercalated reversibly from the MnO2 cathode material at the same time, while the NaTi2 (PO4 )3 anode material can only intercalate/deintercalate Na + . Based on this, we constructed an aqueous sodium-magnesium hybrid ion battery system. The anode is carbon-coated NaTi2 (PO4 )3 material, and the cathode is MnO2 /CNTs composite material. The electrolyte is Na2 SO4 and MgSO4 mixed aqueous solution. The working voltage of the battery is about 1.4 V and its capacity can reach 97 mAh g −1 .